Servant Leadership, Job Characteristics, Psychological Capital, and Innovative Work Behavior as Predictors of Private University Lecturer Job Performance - Mila Hariani; Rahayu Mardikaningsih; Didit Darmawan (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
This quantitative study examines the influence of Servant Leadership, Job Characteristics, Psychological Capital, and Innovative Work Behavior on Job Performance among 147 lecturers from private universities in East Java Province using an accidental sampling technique. Data were analyzed using multiple linear regression. Multiple linear regression analysis revealed that all four independent variables simultaneously affect Job Performance (F = 42.567, p < 0.001, R² = 0.623, Adjusted R² = 0.612). The model explains 62.3% of the variance in Job Performance. Partially, Servant Leadership, Job Characteristics, Psychological Capital, and Innovative Work Behavior each have significant positive effects on Job Performance. Innovative Work Behavior demonstrates the strongest influence (Beta = 0.340, t = 5.613, p < 0.001), followed by Job Characteristics (Beta = 0.314), Servant Leadership (Beta = 0.293), and Psychological Capital (Beta = 0.279). Findings suggest private university management should prioritize innovative work behavior enhancement through innovation incubation programs and rewards. Job characteristics improvement through greater autonomy and constructive feedback also proves important. Servant leadership development through leadership training for deans and program heads needs implementation. Psychological capital development through coaching, mentoring, and resilience training helps lecturers manage work pressure.